A Contemporary Use of Generic drugs in the Healthcare System - Rai, Neeta (Asian Journal of Pharmaceutics (AJP), 2024)
The term “drugs” or “medicines” refers to substances used in the treatment, diagnosis, mitigation, and prevention of disease. However, the price is high. Not for everyone, however, the expense of the medications makes receiving therapy very challenging for lower and middle-class individuals. The patient’s inability to pay for the cost of the medications contributes to a great number of deaths. The health-care system underwent a revolution when generic medications entered the market, and their market share is still growing today. Because these are genuine, trustworthy, safe, affordable, and available to everyone, society’s poor and needy groups benefit. Now, there is a substitute for expensive branded medications. The Indian government is doing a lot to increase access to generic medications in both urban and rural areas, as well as to raise awareness among the public that these medications are just as effective and safe as name-brand medications. Generic medications are produced by numerous pharmaceutical companies and distributed through retail outlets. In addition, operating and delivering generic medications to customers’ homes are e-pharmacies. Numerous Pradhan Mantri Bhartiya Janaushadhi Kendra (PMBJK) locations have been established by the government nationwide, where people can get generic medications for a significantly reduced price. The history of generic medicine shows, how the prices are less than standard medicines and how it can be beneficial for economic factors.